2014
DOI: 10.1007/s00520-014-2554-z
|View full text |Cite
|
Sign up to set email alerts
|

Participation in questionnaire studies among couples affected by breast cancer

Abstract: Socioeconomic characteristics of patients and partners, and morbidity of partners may influence participation in couple-based psychosocial breast cancer research. Breast cancer-related characteristics do not seem to influence participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Nevertheless, this study implies that once sexual minority women are enrolled and given the option of providing contact information for a spouse/partner or other support person, they are likely to have informal caregivers participate. Our other findings, including individual and dyad characteristics related to caregiver participation, are also consistent with previous research in predominantly heterosexual study populations or assuming heterosexuality [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, this study implies that once sexual minority women are enrolled and given the option of providing contact information for a spouse/partner or other support person, they are likely to have informal caregivers participate. Our other findings, including individual and dyad characteristics related to caregiver participation, are also consistent with previous research in predominantly heterosexual study populations or assuming heterosexuality [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…This finding extends research on recruitment and retention of individual breast cancer survivors [41] and may reflect response biases that have been consistently observed throughout epidemiologic [12] and breast cancer literature [15,41,42]. Similarly consistent with previous research, we found that survivors with higher numbers of comorbidities were less likely to have caregivers participate, which may reflect time constraints or lower quality of life among caregivers [14,15]. In addition to the study design and recruitment considerations discussed below, these individual characteristics of survivors that relate to their caregivers' participation should be carefully assessed as potential sources of participation bias in future dyad-focused research and practice.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations